Reconstructing identities and alterities in Ancient Greece - Gabrecht, Ana Penha (Romanitas - Revista de Estudos Grecolatinos, 2013)
Review of: SKINNER, Joseph Edward. The invention of Greek ethnography: from Homer to Herodotus. New York: Oxford University Press, 2012. 343 p.
Keywords: Greek History; Ethnography; Homer; Herodotus